EDUCAÇÃO PROFISSIONAL: CRÍTICA À IMPLANTAÇÃO DO PROJETO ENSINO MÉDIO INTEGRADO DO ESTADO DO CEARÁ | Professional education: criticism to implantation of Integrated Secondary Education in the State of Ceará (Trabalho & Educação, 2016)
The article has a bibliographic theoretical nature, aims to analyze the implementation of the proposed Integrated Secondary Education in the State in Ceará, which was accomplished through the creation of the State Schools of Professional Education (EEEPs). This paper analyzes the integration of secondary level professional education modality meets the challenge of providing for workers’ children a school with quality, while contributing to the elevation of the discrete social indices achieved by the State of Ceará. The methodology used in this work is documentary-bibliographic, and are based mainly on the analysis of documents that give legal and philosophical support to vocational education policy in the state of Ceará, in the last decade, such as the Resolution No. 6/2012, which deals with the National Curriculum Guidelines for Vocational and Technical High School Education, state law n ̊11.741 / 08, and the documents adopted by the Social Institute of Co-responsibility, such as the social and educational Entrepreneurial Technology (TESE – acronym en Portuguese) arising from the Company Theory Odebrecht (TEO ). We can infer that the Integrated School project of Ceará has a vocational training deeply related to market needs, while moves away of the interests of workers and of a development model that favors the whole of society.__O artigo tem como objetivo principal refletir sobre a implantação da proposta Ensino Médio Integrado do Estado do Ceará, que se efetivou por intermédio da criação das Escolas Estaduais de Educação Profissional (EEEP). O presente trabalho analisa a integração do nível médio à modalidade educação profissional e em que medida atende ao desafio de disponibilizar para os filhos dos trabalhadores uma escola de qualidade, ao mesmo tempo que contribui para a melhoria dos discretos índices sociais do Estado do Ceará. A metodologia utilizada neste trabalho tem caráter documental-bibliográfico, pautando-se, sobretudo, pela análise de documentos que dão suporte legal e filosófico à política de educação profissional no Estado do Ceará na última década, tais como a Resolução no 6/2012, que trata das Diretrizes Curriculares Nacionais para a Educação Profissional Técnica de Nível Médio, a Lei estadual no 11.741/08, bem como os documentos adotados pelo Instituto de Corresponsabilidade Social, a exemplo da Tecnologia Empresarial Socio Educacional (TESE), oriunda da Teoria Empresarial Odebrecht (TEO). Podemos aferir que o projeto Ensino Médio Integrado do Estado do Ceará apresenta uma formação profissional profundamente relacionada às necessidades do mercado, ao mesmo tempo que se distancia dos interesses dos trabalhadores e de um modelo de desenvolvimento que favoreça o conjunto da sociedade.